Japan's Quest for Growth : Exploring the Role of Capital and innovation - Syed, Murtaza (IMF Working Papers; Working Paper, 2010)
As labor input in Japan shrinks with population aging, capital accumulation and productivity gains will drive growth over the medium-term. At the same time, a changing global landscape calls for a shift in export-oriented investment toward new markets and a new generation of products, as well as increased investment by domestically-oriented firms. What policies could be adopted to help firms adjust to the imperatives of the post-crisis global economy and boost medium-term growth? Using disaggregated data, this paper investigates the determinants of investment and R and D spending by Japanese firms. The results suggest that policies could usefully focus on four areas. First, raising the return on investment, including through reforms to the tax code. Second, decreasing uncertainty through improved risk management by firms and by bolstering the business climate. Third, improving SME access to finance, notably by encouraging venture capital investment in innovative areas and more risk-based lending. And fourth, reducing excess leverage and supporting corporate restructuring to enable new investments to flourish.